Making sense of the electronic resource marketplace: trends in health-related electronic resources. - Blansit, B D (1999)
Changes in the practice of medicine and technological developments offer librarians unprecedented opportunities to select and organize electronic resources, use the Web to deliver content throughout the organization, and improve knowledge at the point of need. The confusing array of available products, access routes, and pricing plans makes it difficult to anticipate the needs of users, identify the top resources, budget effectively, make sound collection management decisions, and organize the resources effectively and seamlessly. The electronic resource marketplace requires much vigilance, considerable patience, and continuous evaluation. There are several strategies that librarians can employ to stay ahead of the electronic resource curve, including taking advantage of free trials from publishers; marketing free trials and involving users in evaluating new products; watching and testing products marketed to the clientele; agreeing to beta test new products and services; working with aggregators or republishers; joining vendor advisory boards; benchmarking institutional resources against five to eight competitors; and forming or joining a consortium for group negotiating and purchasing. This article provides a brief snapshot of leading biomedical resources; showcases several libraries that have excelled in identifying, acquiring, and organizing electronic resources; and discusses strategies and trends of potential interest to biomedical librarians, especially those working in hospital settings.